Ocular Immune Privilege and Ocular Melanoma: Parallel Universes or Immunological Plagiarism? - Niederkorn, Jerry Y. (Frontiers in Immunology, 2012)
Evidence of immune privilege in the eye was recorded almost 140 years ago, yet interest in immune privilege languished for almost a century. However, the past 35 years have witnessed a plethora of research and a rekindled interest in the mechanisms responsible for immune privilege in the anterior chamber of the eye. This research has demonstrated that multiple anatomical, structural, physiological, and immunoregulatory processes contribute to immune privilege and remind us of the enormous complexity of this phenomenon. It is widely accepted that immune privilege is an adaptation for reducing the risk of immune-mediated inflammation in organs such as the eye and brain whose tissues have a limited capacity to regenerate. Recent findings suggest that immune privilege also occurs in sites where stem cells reside and raise the possibility that immune privilege is also designed to prevent the unwitting elimination of stem cells by immune-mediated inflammation at these sites. Uveal melanoma arises within the eye and as such, benefits from ocular immune privilege. A significant body of research reveals an intriguing parallel between the mechanisms that contribute to immune privilege in the eye and those strategies used by uveal melanoma cells to evade immune elimination once they have disseminated from the eye and establish metastatic foci in the liver. Uveal melanoma metastases seem to have “plagiarized” the blueprints used for ocular immune privilege to create “ad hoc immune privileged sites” in the liver.